ANALYSIS OF THE LEGAL PROVISION OF ISLAM AND THE MECHANISM OF LIFE INSURANCE - Kamaluddin, Imam; Nisak, Radhiyatun (Universitas Islam Negeri Mataram, 2024)
Islamic life insurance is a rapidly growing economic product in the Islamic economic environment. Although there are regulations and fatwas that regulate the mechanism and law of Islamic life insurance, scholars still have differing opinions about its permissibility. This paper aims to analyze Islamic fiqh about the law and mechanism of Islamic life insurance. The research method used is qualitative research with an empirical juridical approach. The analysis results show two main views among scholars regarding the permissibility of Islamic life insurance. Opinions allowing sharia life insurance refer to the principles of sharia and see it as a means of protection that can benefit the community. On the other hand, some opinions reject Islamic life insurance because it is considered to violate the fundamental principles of Islam, such as belief in God's destiny and avoidance of the elements of usury, gharar, and maisir. In the Indonesian context, the National Sharia Council (DSN) of MUI has issued fatwas and regulations related to the mechanism and law of Islamic life insurance. This fatwa is a solution to the two views of fiqh scholars and follows the principles of maqasid sharia.